Influence of CYP2B6 polymorphisms on the persistence of plasma nevirapine concentrations following a single intra-partum dose for the prevention of mother to child transmission in HIV-infected Thai women - Soranun Chantarangsu (2018)
Objectives: To investigate the association of single nucleotide polymorphisms (SNPs) with nevirapine concentrations following intra-partum single-dose nevirapine. Methods: Plasma and DNA samples were obtained from 330 HIV-infected Thai women who received intra-partum single-dose nevirapine in the PHPT-2 clinical trial to prevent perinatal HIV transmission. Nine SNPs within CYP2B6, CYP3A4 and ABCB1 were genotyped by real-time PCR. Nevirapine plasma concentrations were determined by HPLC and used in a population pharmacokinetic analysis. Results: Higher nevirapine exposure was observed in women carrying the CYP2B6 516G>T polymorphism, but this did not reach statistical significance (P = 0.054). The TGATC CYP2B6 haplotype (g.3003T, 516G, 785A, g.18492T and g.21563C) was associated with increased nevirapine clearance and lower exposure (P = 0.0029). The median time for nevirapine concentrations to reach 10 ng/mL post-partum (nevirapine IC50for HIV-1) was 14 days [interquartile range (IQR, 14-18)] for TGATC homozygotes, 16 days (14-20) for TGATC heterozygotes and 18 days (14-20) for non-TGATC homozygotes (P = 0.020). Conclusions: The CYP2B6 516G>T impact on nevirapine concentrations was less pronounced after intra-partum single-dose nevirapine than reported under steady-state conditions, perhaps due to lack of enzyme auto-induction at the time of dosing. Although the TGATC CYP2B6 haplotype may shorten the persistence of nevirapine post-partum, its practical implications for the prevention of HIV transmission or selection of resistance mutations are likely limited. © The Author 2009. Published by Oxford University Press on behalf of the British Society for Antimicrobial Chemotherapy.